Active electroceutical treatment of Pseudomonas aeruginosa infected murine wounds - Colin R. Mack; Traci A. Wilgus; Sheri Dellos-Nolan; Tony DiCesare; Daria Bentley; Fraser J. Daniel; Vish V. Subramaniam; Sahil Mahajan; Paul Stoodley; Daniel J. Wozniak; Shaurya Prakash (PLoS ONE, 2025)
Chronic, infected dermal wounds have a high burden of cost and remain a persistent hurdle within healthcare. Electroceutical dressings that deliver antimicrobial agents directly to the wound site have emerged as an alternative solution to current standards of care. Here, through a systematic evaluation in an infected murine wound model we report on an actively powered electroceutical dressing that generates hypochlorous acid in situ as an antimicrobial agent to clear infection. In a significant new discovery, we also report that the treatment of these infected wounds with the actively powered electroceutical promotes the closure of wounds better than other test conditions. In a 10-day murine study, mice were wounded, and the dermal injury was infected with Pseudomonas aeruginosa. Four treatment plans were administered to these wounds: no treatment, a commercially available electroceutical dressing, and our electroceutical dressing both powered and unpowered. The mice were subsequently sacrificed 8 days post infection. The powered electroceutical dressing demonstrated significantly reduced bacterial burden compared to untreated wounds. The powered electroceutical dressing also showed the highest wound closure with nearly 60% wound area reduction and approximately 36% percent re-epithelization of the wound bed in contrast to the no-treatment case. When compared against the other treatments, the powered electroceutical dressing demonstrated an improved capability in promoting wound area reduction while lowering infection burden.